The Huk rebellion a study of peasant revolt in the Philippines - Kerkvliet, Benedict J.; iGLibrary (online resource). (Berkeley University of California Press, 1977)
Newly available with an updated bibliographic essay, this highly acclaimed work explores the Huk rebellion, a momentous peasant revolt in the Philippines. Unlike prevailing top-down analysis, Kerkvliet seeks to understand the movement from the point of view of its participants and sympathizers. He argues that seeing a peasant revolt through the eyes of those who rebelled explains and clarifies the actions of people who otherwise might appear irrational. Drawing on a rich array of documents and in-depth interviews with peasants and rebel leaders, the author provides definitive answers to the causes of the rebellion, the goals of the rebels, and the process of resistance.
The Huk rebellion: a study of peasant revolt in the Philippines -- Dedication -- Contents -- Author's Note -- Preface to the Second Printing -- Preface to the First Printing -- Notations for Footnotes -- Chapter 1: Origins of Rebellion -- Chapter 2: Unrest -- Chapter 3: The Hukbalahap: Resistance to the Japanese Occupation in Central Luzon -- Chapter 4: Prelude to Rebellion -- Chapter 5: Rebellion: 1946 - 1948 -- Chapter 6: The Rise and Fall -- Chapter 7: Conclusion -- Acknowledgments -- Glossary -- Bibliographic Essay on Recent Publications -- Bibliography -- Index.
Includes bibliographical references and index.
Electronic Reproduction.
Keywords: Huks; Peasant uprising -- Philippines; Electronic books; Philippines -- Politics and government -- 1935-1946.; Philippines -- History -- 1946-1986.